2019
DOI: 10.1111/are.14322
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of multiple antibiotic resistance and genotypic characterization inEdwardsiella tardaisolated from cage‐cultured hybrid red tilapia (Oreochromissp.) in the Ping River, Northern Thailand

Abstract: Edwardsiella tarda is a pathogen that causes edwardsiellosis in aquatic animals. The emergence of multiple antibiotic‐resistant strains makes antibiotic treatment difficult. This study aimed to investigate the antibiotic susceptibility patterns and the genotypic characterization of E. tarda isolated from cage‐cultured red tilapia in Thailand. A total of 30 isolates were identified as E. tarda using biochemical and molecular analysis. The disc diffusion method for testing antibiotic susceptibility showed all th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 47 publications
(68 reference statements)
4
22
1
Order By: Relevance
“…It was reported that E.tarda is naturally resistant to macrolides and glycopeptides (Stock and Wiedemann 2001) which is in close agreement with the present finding. Niu et al (2019) also documented the multidrug resistance of E. tarda associated with Tilapia towards tetracyclines, sulphonamides and beta-lactams; which supported the present finding. The establishment of multiple antimicrobial resistance in the fish pathogens affects the successful antibiotic treatment.…”
Section: Antibiotic Resistance Pattern Before and After Plasmid Curingsupporting
confidence: 91%
“…It was reported that E.tarda is naturally resistant to macrolides and glycopeptides (Stock and Wiedemann 2001) which is in close agreement with the present finding. Niu et al (2019) also documented the multidrug resistance of E. tarda associated with Tilapia towards tetracyclines, sulphonamides and beta-lactams; which supported the present finding. The establishment of multiple antimicrobial resistance in the fish pathogens affects the successful antibiotic treatment.…”
Section: Antibiotic Resistance Pattern Before and After Plasmid Curingsupporting
confidence: 91%
“…GBS and S. iniae were found to be susceptible to most of the antimicrobials tested in the present study, showing that OTC, ENR and AML were effective for the control of those pathogens. However, the occurrence of MDR bacteria in aquaculture in Thailand has been reported (Niu, Wongsathein, Boonyayatra, & Khattiya, ; Tipmongkolsilp et al, ). The upshot is that monitoring of the usage of antimicrobials is crucial to reducing potential risks to environmental and human health.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no effective commercial vaccine available, and antimicrobial-medicated feeds are still a commonly used strategy to control edwardsiellosis (Leung et al 2019 ). The occurrence of multiple antibiotic-resistant E. piscicida is presently very common (Lo et al 2014 ; Niu et al 2019 ). For example, its resistance to oxytetracycline and ampicillin ranges from 21 to 90% and 73.3 to 100.0%, respectively (Lo et al 2014 ; Niu et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of multiple antibiotic-resistant E. piscicida is presently very common (Lo et al 2014 ; Niu et al 2019 ). For example, its resistance to oxytetracycline and ampicillin ranges from 21 to 90% and 73.3 to 100.0%, respectively (Lo et al 2014 ; Niu et al 2019 ). Approximately 70% of isolates from red tilapia in northern Thailand were resistant to at least seven antibiotics (Niu et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%